Prepreg, fiber-reinforced plastic using the same, and method for producing fiber-reinforced plastic
By using a prepreg composed of cyclic ester to perform annular polymerization reaction with accelerator and fibers, the shortcomings of existing thermoplastic epoxy resins in terms of solvent resistance are solved, and fiber-reinforced plastics with high strength and good solvent resistance are achieved.
Patent Information
- Application Number
- JP2023163219
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-07
AI Technical Summary
In the present invention, the -situ polymeric thermoplastic epoxy resin has poor solubility to organic solvents after molding, which limits its application in coating parts.
Using a prepreg composed of cyclic esters, fiber reinforced plastics with high strength and good solvent resistance are prepared by ring-opening polymerization reaction with accelerator and fibers.
The high strength and excellent solvent resistance of fiber reinforced plastics are achieved, expanding their application potential in coated parts.
Smart Images

Figure 2025054042000001 
Figure 2025054042000002 
Figure 2025054042000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a prepreg, a fiber-reinforced plastic using the prepreg and having high strength and excellent solvent resistance, and a method for producing the same. [Background technology]
[0002] Fiber-reinforced plastics (FRP) have excellent physical properties such as light weight and high strength, and are used in many fields. Among them, those using carbon fiber as the reinforcing fiber (CFRP) are known to have particularly excellent mechanical strength.
[0003] Epoxy resins are mainly used as the base resin for FRP because of their excellent balance between price and physical properties. A method has been proposed in which epoxy compounds and / or phenolic hydroxyl group-containing compounds are mixed with reinforcing fibers in advance, polymerized by polyaddition reaction using a polymerization catalyst, and fiber-reinforced thermoplastic resin is molded. This epoxy resin is also called in-situ polymerization thermoplastic epoxy resin, and FRP using this is expected to be excellent in mass production, moldability, and recyclability. In-situ polymerization thermoplastic epoxy resins have good impregnation properties because they are impregnated into fibers in a low viscosity state before polymerization, and the proportion of reinforcing fibers can be increased, and they have excellent impact strength and toughness compared to general-purpose thermosetting epoxy resins. In addition, various polymerization systems such as polyurethane and acrylic resins as well as epoxy resins have been reported for in-situ polymerization thermoplastic resins due to their moldability in fine, large, and complex shapes, and their strength reduction due to the suppression of air bubble generation at the resin / reinforcing fiber interface.
[0004] However, the in-situ polymerization type thermoplastic epoxy resin described in Patent Document 1 has poor solvent resistance even after being molded into a molded article, and its application to components that are painted with paints containing organic solvents is limited. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2004 / 060981 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a prepreg, a fiber-reinforced plastic using the prepreg and having high strength and excellent solvent resistance, and a method for producing the same. [Means for solving the problem]
[0007] In order to solve the above problems, the inventors conducted extensive research into a wide variety of FRP base resins other than epoxy resin-based resins, and discovered that a fiber-reinforced plastic using a prepreg made of a cyclic ester composition containing a cyclic ester compound and a polymerization catalyst and reinforcing fibers has high strength and excellent solvent resistance, thereby completing the present invention.
[0008] That is, the present invention relates to a prepreg using a cyclic ester composition containing a cyclic ester compound and a polymerization catalyst, and reinforcing fibers.
[0009] The cyclic ester compound is preferably at least one selected from lactones and / or dilactones, and among these, at least one selected from ε-caprolactone, glycolide, and lactide.
[0010] The polymerization catalyst is preferably a compound containing at least one metal element selected from the group consisting of alkaline earth metals, rare earth metals, third row transition metals, aluminum, germanium, tin, and antimony, and / or a carboxylate, alkoxide, aryloxide, or β-diketone enolate of the metal element in the compound.
[0011] The polymerization catalyst is more preferably at least one selected from tin octoate, titanium tetraisopropoxide, and aluminum triisopropoxide, and the cyclic ester compound is preferably at least one selected from ε-caprolactone, glycolide, and lactide.
[0012] The reinforcing fibers preferably have a fiber length of 10 mm or more.
[0013] The cyclic ester composition preferably has a viscosity at 100° C. of 100 Pa·s or less.
[0014] The present invention also relates to a fiber-reinforced plastic using the above prepreg.
[0015] The present invention also provides a method for producing the fiber-reinforced plastic, comprising the steps of: a mixing step of mixing a cyclic ester compound with a polymerization catalyst to obtain a mixture (cyclic ester composition); a prepregging step of obtaining a prepreg from the mixture (cyclic ester composition) and reinforcing fibers; a polymerization step of causing ring-opening polymerization of a cyclic ester compound in the prepreg; The present invention relates to a method for producing a fiber-reinforced plastic, comprising the steps of: Effect of the Invention
[0016] The prepreg of the present invention can provide a fiber reinforced plastic (FRP) having high strength and excellent solvent resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below based on preferred embodiments thereof. The prepreg of the present invention includes a cyclic ester composition containing a cyclic ester compound and a polymerization catalyst, and a reinforcing fiber as essential components. Here, the cyclic ester composition is a composition that contains a cyclic ester compound and a polymerization catalyst as essential components, and is polymerized by heating to become a thermoplastic polyester. This cyclic ester composition may include additives such as an organic solvent, a filler, or a flame retardant.
[0018] The cyclic ester compound used in the cyclic ester composition may have one or more ester moieties in the molecule. However, in the case of a cyclic ester compound having multiple ester moieties, the cyclic ester compound is a polymer produced from one type of compound. Lactones having one ester moiety in the molecule, dilactones having two ester moieties in the molecule, etc. can be used as the cyclic ester compound. These lactones or dilactones may be used alone or in combination of multiple types.
[0019] Examples of lactones include ε-caprolactone (oxacycloheptan-2-one), p-dioxanone (1,4-dioxan-2-one), β-propiolactone (oxetan-2-one), δ-valerolactone (oxacyclohexane-2-one), γ-valerolactone (5-methyloxolan-2-one), β-butyrolactone (4-methyloxetan-2-one), γ-butyrolactone (oxolan-2-one), and pivalolactone (3,3-dimethyloxetan-2-one).
[0020] Examples of dilactones include lactide (3,6-dimethyl-1,4-dioxane-2,5-dione), glycolide (1,4-dioxane-2,5-dione), tetramethyl glycolide, ethylene oxalate (1,4-dioxane-2,3-dione), and ethylene brassylate (2,5-dioxacycloheptadeca-1,6-dione).
[0021] In order to increase the strength of fiber reinforced plastics, ε-caprolactone, glycolide or lactide is preferred, and lactide is more preferred.
[0022] The cyclic ester compound may contain impurities such as raw materials, oligomers, polymers, etc. The purity of the cyclic ester compound is sufficient to be 90% by weight or more, and more preferably 95% by weight or more.
[0023] In particular, when lactide is used, from the viewpoint of solvent resistance, if the lactide used is an L-lactide, the D-lactide content is preferably 0 to 10 mol %, more preferably 0 to 5 mol %, and even more preferably 0 to 3 mol %.
[0024] In the cyclic ester composition of the present invention, the blending amount of the cyclic ester compound is preferably 50 to 100% by weight. If it is less than 50% by weight, the solvent resistance tends to deteriorate when the cyclic ester composition of the present invention is polymerized to form a fiber reinforced plastic. It is more preferably 70 to 100% by weight.
[0025] The cyclic ester composition of the present invention contains a polymerization catalyst as an essential component. Examples of the polymerization catalyst include compounds containing at least one metal element selected from the group consisting of alkaline earth metals, rare earth metals, third period transition metals, aluminum, germanium, tin, and antimony. Examples of alkaline earth metals include magnesium, calcium, and strontium. Examples of rare earth elements include scandium, yttrium, lanthanum, and cerium. Examples of transition metals of the third period include iron, cobalt, nickel, zinc, and titanium. The polymerization catalyst is preferably a compound of at least one metal selected from the group consisting of tin, titanium, and aluminum. The polymerization catalyst can be added in the form of a carboxylate, alkoxide, aryloxide, or enolate of β-diketone of these metals. In consideration of the polymerization activity and color, tin octylate, titanium tetraisopropoxide, and aluminum triisopropoxide are particularly preferred.
[0026] The amount of the polymerization catalyst is preferably 0.001 to 5.0% by weight based on the cyclic ester compound. If it is less than 0.001% by weight, it may take a long time to complete the polymerization in the on-site polymerization, which may result in a decrease in productivity, and may be deactivated before the target molecular weight is reached. On the other hand, if it exceeds 5.0% by weight, the polymerization reaction may proceed quickly, but storage stability may be impaired, causing problems in process compatibility. It is more preferably 0.01 to 1.0% by weight.
[0027] The cyclic ester composition of the present invention may use an alcohol as a polymerization initiator. The alcohol is preferably non-volatile and does not inhibit the ring-opening polymerization of the cyclic ester compound, and is preferably a higher alcohol such as decanol, dodecanol, tetradecanol, hexadecanol, or octadecanol.
[0028] The amount of the polymerization initiator is preferably 0.001 to 5.0% by weight based on the cyclic ester compound. If it is less than 0.001% by weight, it may take a long time to complete the polymerization in the on-site polymerization, which may reduce productivity, and may be deactivated before the target molecular weight is reached. On the other hand, if it exceeds 5.0% by weight, it may participate in the polymerization reaction but not be incorporated into the skeleton, which may impair the physical properties of the resin after polymerization. More preferably, it is 0.01 to 1.0% by weight.
[0029] The cyclic ester composition of the present invention desirably does not contain an organic solvent, but may contain an organic solvent as a solvent for the polymerization catalyst or for viscosity adjustment, if necessary. The organic solvent is not particularly limited as long as it does not inhibit the polymerization reaction of the cyclic ester composition, but hydrocarbons, ketones, and ethers are preferred because of their ease of availability. Specific examples include toluene, xylene, acetone, methyl ethyl ketone, isobutyl ketone, cyclopentanone, cyclohexanone, and diethylene glycol dimethyl ether. However, if a large amount of organic solvent is present, it may inhibit the polymerization reaction, and if the organic solvent remains in the polymer, it may deteriorate the mechanical properties and heat resistance. In addition, compounds containing a substituent having active hydrogen such as alcohol, carboxylic acid, and amine are not preferred because they may inhibit the ring-opening reaction of the cyclic ester compound. For this reason, when an organic solvent is blended, the proportion thereof is 10% by weight or less in the cyclic ester composition, preferably 5% by weight or less, and particularly preferably 2% by weight or less. When an organic solvent is added, there is no lower limit, but it is usually preferable that the organic solvent be contained in an amount of 0.01% by weight or more, and more preferably 0.5% by weight or more.
[0030] The cyclic ester composition of the present invention desirably has a low viscosity in order to maintain the impregnation property into the reinforcing fiber. The viscosity when heated to 100°C is preferably 100 Pa·s or less, more preferably 50 Pa·s or less, and even more preferably 10 Pa·s or less. The time required for the viscosity to double from the initial viscosity (viscosity doubling time) is preferably 10 minutes or more, more preferably 30 minutes or more, and even more preferably 60 minutes or more.
[0031] The progress of polymerization of the cyclic ester compound in the cyclic ester composition of the present invention may be judged by the transition of the weight average molecular weight of the polymer. The polymerization atmosphere is preferably performed under vacuum or under an inert gas such as nitrogen or argon. The polymerization temperature is preferably 120 to 260°C, more preferably 140 to 220°C, because polymerization does not proceed sufficiently if it is less than 120°C, and decomposition reaction is promoted if it exceeds 260°C. The polymerization time is preferably 15 to 240 minutes, more preferably 30 to 180 minutes, because polymerization does not proceed sufficiently if it is less than 15 minutes, and molecular weight starts to decrease due to side reactions if it exceeds 240 minutes. The polymerization reaction is affected by the polymerization temperature and polymerization time, so there is no limiting condition setting, but for example, at the above-mentioned 140°C to 220°C, the polymerization time is preferably more than 60 minutes.
[0032] The weight average molecular weight (Mw) of the polymer obtained by polymerizing (ring-opening polymerization) the cyclic ester compound in the cyclic ester composition of the present invention is preferably 50,000 to 300,000. If the Mw of the polymer is less than 50,000, the polymer contains a large amount of compounds that have not been sufficiently polymerized, and there is a risk of the solvent resistance being deteriorated. On the other hand, if the Mw of the polymer exceeds 300,000, there is a risk of the processability being impaired when made into a fiber-reinforced plastic. More preferably, it is 50,000 to 250,000, and even more preferably, it is 70,000 to 250,000.
[0033] The cyclic ester composition of the present invention may contain various additives, such as fillers such as fumed silica, flame retardants such as aluminum hydroxide and red phosphorus, modifiers such as core-shell rubber, viscosity adjusters such as xylene resin, plasticizers, antioxidants, light stabilizers, ultraviolet absorbers, heat stabilizers, lubricants, release agents, antistatic agents, antibacterial and antifungal agents, crystallization nucleating agents, and colorants including dyes and pigments.
[0034] The cyclic ester composition of the present invention becomes a thermoplastic plastic by polymerizing (ring-opening polymerization) the cyclic ester compound. This thermoplastic plastic has excellent adhesion to various fibers as a resin component of fiber-reinforced plastics.
[0035] The prepreg of the present invention can be obtained by using the above-mentioned cyclic ester composition and reinforcing fibers, and can be obtained by impregnating the reinforcing fibers with the cyclic ester composition, but is not limited thereto.
[0036] For example, the prepreg can be obtained as follows. That is, the cyclic ester composition of the present invention is coated on a release-treated paper or plastic film, and a release-treated cover film is applied as necessary to obtain a cyclic ester composition film. The release paper, release plastic film, and cover film can be known and are not particularly limited. The thickness of the cyclic ester composition film is determined by the design thickness of the prepreg and the ratio of the composition, and the normal thickness is 1 μm or more and 300 μm or less. If the reinforcing fiber is not defibrated cleanly, there is a tendency for the opening of the fiber to become noticeable, and if it exceeds 300 μm, it becomes difficult to uniformly impregnate the continuous reinforcing fiber. It is preferably 5 μm or more and 150 μm or less, and more preferably 10 μm or more and 100 μm or less.
[0037] Next, reinforcing fibers are arranged in parallel to the composition-coated surface of the obtained cyclic ester composition film, and the reinforcing fibers are impregnated with the composition. Alternatively, after arranging the reinforcing fibers, the composition-coated surface of another cyclic ester composition film is overlapped to form a sandwich structure, and then the composition is impregnated into the reinforcing fibers by passing through a heated roll. In addition, a prepreg can be obtained in this way. In the prepreg, although there is no limitation, the content Rc of the cyclic ester composition is preferably 5 to 99%.
[0038] The reinforcing fibers used in the present invention are intended to reinforce plastics, such as carbon fibers, glass fibers, aramid fibers, basalt fibers, cellulose fibers, plant fibers, and animal fibers, and are not particularly limited. As plant fibers, jute, linen, ramie, hemp, cotton, kapok, kenaf, palm, coconut fiber, poplar cotton, rice straw, wheat straw, pineapple fiber, bamboo fiber, and the like can be used. As animal fibers, silk and wool can be used. As for the form of the fibers, UD sheets, woven fabrics, tow, chopped fibers, nonwoven fabrics, papermaking, and the like in which the fibers are aligned can be used, and are not particularly limited. However, from the viewpoint of impregnation, the thickness of each fiber bundle is preferably 1 mm or less, more preferably 0.5 mm or less, and even more preferably 0.2 mm or less.
[0039] From the viewpoint of improving the strength of the fiber-reinforced plastic, the reinforcing fibers preferably have a fiber length of 10 mm or more, and more preferably are long fibers or continuous long fibers of 20 mm or more. The fiber bundle preferably has a fineness of 100 to 2000 tex, and the weight per unit area (basis weight) is preferably 10 to 500 g / m 2 It is preferable that:
[0040] The ratio by weight of the reinforcing fibers to the cyclic ester composition is preferably 2:8 to 8:2. If the ratio of the reinforcing fibers is too low, the strength required for the fiber-reinforced material may not be fully satisfied, and if the ratio of the reinforcing fibers is too high, defects such as voids may occur.
[0041] The fiber reinforced plastic of the present invention can be obtained by polymerizing (ring-opening polymerization) the cyclic ester compound in the prepreg, that is, through the following steps.
[0042] When using a prepreg, first, the cyclic ester compound and the polymerization catalyst are mixed to obtain a mixture (cyclic ester composition) (mixing step). Next, a prepreg is obtained from the mixture (cyclic ester composition) obtained in the mixing step and reinforcing fibers (prepregging step). As for this prepregging step, the method of passing through the cyclic ester composition film described above can be preferably mentioned. Then, the cyclic ester compound in the prepreg obtained in the prepregging step is polymerized (ring-opening polymerization) (polymerization step). Here, a plurality of prepregs may be used, and they can also be used by laminating. The polymerization conditions (atmosphere, temperature, time) are as described above. As the polymerization method, for example, a known method such as vacuum pressing can be mentioned. When using a prepreg, the fiber-reinforced plastic of the present invention consisting of a thermoplastic plastic and reinforcing fibers can be obtained by passing through such a mixing step, prepregging step, and polymerization step.
[0043] The fiber reinforced plastic of the present invention thus obtained has excellent solvent resistance and flexural properties (flexural strength, flexural modulus). These properties can be preferably evaluated by the method described in the Examples. For example, the flexural strength is preferably 80 MPa or more, more preferably 90 MPa or more. Also, the flexural modulus is preferably 4.0 GPa or more. EXAMPLES
[0044] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. Unless otherwise specified, "parts" refers to parts by weight, and "%" refers to % by weight.
[0045] The raw materials, catalysts, etc. used in the examples are as follows.
[0046] [Cyclic ester compounds] A1: L-(-)-lactide (Tokyo Chemical Industry Co., Ltd., purity >98.0% (volumetric analysis method (T)), D-isomer ratio 2.5 mol%) [ka] A2: ε-caprolactone (Tokyo Chemical Industry Co., Ltd., purity >99.0% (gas chromatography (GC))) [ka]
[0047] [Epoxy resin composition] A3: Molten mixture of bisphenol A type epoxy resin / bisphenol A (precursor mixture of epoxy resin composition)
[0048] [Polylactic acid] A4: Polylactic acid (Nature Works, 4032D)
[0049] [Polymerization catalyst] B1: Stannous octoate (2-ethylhexyl stannous (II)) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) B2: Tris(p-methoxyphenyl)phosphine (TPAP, manufactured by Hokko Chemical Industry Co., Ltd.)
[0050] [Polymerization initiator] C1: Stearyl alcohol (Tokyo Chemical Industry Co., Ltd.)
[0051] [Reinforced fiber] D1: Carbon fiber (Toray Industries, Inc., T700-12K-50C, UD material, fiber length 300 mm, basis weight 150 g / m 2 ) D2: Glass fiber (manufactured by Nitto Boseki Co., Ltd., WEA 7628 XS13, cloth material, fiber length 300 mm, basis weight 209 g / m 2 ) D3: Cotton fiber (manufactured by Toyobo Fibers Co., Ltd., UD material, fiber length 300 mm, basis weight 109 g / m 2 ) D4: Jute fiber (made by Janata, cloth material, fiber length 300 mm, basis weight 310 g / m 2 )
[0052] The evaluation methods used in the examples are as follows.
[0053] Weight average molecular weight (Mw): The weight average molecular weight (Mw) was determined by GPC measurement. Specifically, a main body HLC8420GPC (manufactured by Tosoh Corporation) equipped with columns (TSKgel SuperHM-H, SuperHM-H, both manufactured by Tosoh Corporation) in series was used, and the column temperature was set to 40°C. Chloroform was used as the eluent, with a flow rate of 0.6 mL / min, and a differential refractive index detector was used as the detector. 50 μL of the measurement sample was prepared by dissolving 0.1 g of solid content in 10 mL of chloroform and filtering through a 0.45 μm microfilter. Mw was calculated by conversion from a calibration curve obtained from standard polystyrene (manufactured by Tosoh Corporation, PStQuick A, PStQuick B, PStQuick C). Data processing was performed using a GPC workstation EcoSEC Elite-WS manufactured by Tosoh Corporation.
[0054] Solvent Resistance: The solvent resistance of fiber-reinforced plastic was evaluated by immersing a sample (fiber-reinforced plastic) 1 mm thick and 10 mm in each direction in 10 mL of tetrahydrofuran (THF) for 24 hours. Samples in which there was no change in the base material and the fibers did not dissolve were marked with an O (pass), samples in which the base material completely dissolved and the fibers dissolve were marked with an X (fail), and samples in which only part of the base material dissolved were marked with a △.
[0055] Flexural strength and flexural modulus: The bending strength and bending modulus of fiber reinforced plastic (FRP) were measured in accordance with JIS K7074, with the fiber orientation of the FRP at 90 degrees (perpendicular) to the input of bending load. The test was performed using a Shimadzu Science Autograph AGS-X, with the sample (fiber reinforced plastic) dimensions of 2 mm thick, 100 mm long, and 15 mm wide, a bending span of 70 mm, and a test speed of 1 mm / min.
[0056] Example 1 100 parts of L-(-)-lactide (A1) was weighed as a cyclic ester compound and sealed in a metal can. The metal can was then placed in a hot air circulating oven preheated to 180°C under a nitrogen atmosphere for 30 minutes to dissolve the cyclic ester compound, and then taken out and cooled to 100°C. 0.1 parts of tin octoate (2-ethylhexyl tin(II)) (B1) was added as a polymerization catalyst to the cyclic ester compound at 100°C, and the mixture was mixed for 2 minutes under vacuum conditions (vacuum degree 4 kPa) at a rotation speed of 2000 rpm using a centrifugal mixer (manufactured by Shinki Corporation, Awatori Rentaro, ARV-310). After mixing, the mixture was quickly removed and immediately cooled to 40°C or lower to obtain a cyclic ester composition.
[0057] The obtained cyclic ester composition was heated to 100°C, and coated on a release paper (casting paper for carbon fiber composite materials, manufactured by Lintec Corporation) as a film substrate using an applicator preheated to a predetermined temperature to obtain a coating film of the composition. The film thickness of the obtained composition film was 34 μm.
[0058] Carbon fibers (D1) were arranged in parallel as reinforcing fibers on the composition-coated surface of the obtained composition film, and the composition-coated surface of another composition film was placed on top of it to form a sandwich structure. This was passed through a heated roll at 100°C for impregnation to obtain a prepreg with a composition content Rc of 35%.
[0059] The release paper was then peeled off from the prepreg, and 13 sheets were laminated with the same fiber orientation direction, sandwiched between release films, and vacuum pressed at 160°C, 0.1 MPa, and 180 minutes using a vacuum press to polymerize the cyclic ester compound and obtain a fiber-reinforced plastic. The Mw of the fiber-reinforced plastic obtained was 100,000, the solvent resistance was ○ (passed), the flexural strength was 90 MPa, and the flexural modulus was 6.5 GPa.
[0060] Comparative Example 1 100 parts of a bifunctional epoxy resin (YD-128, manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent 186 g / eq.) and 60 parts of bisphenol A (manufactured by Nippon Steel Chemical & Material Co., Ltd., hydroxyl equivalent 114 g / eq.) were weighed out, pulverized and mixed using a Henschel mixer, and then sealed in a metal can. The metal can was then left to stand in a hot air circulating oven preheated to 180°C for 30 minutes to dissolve the resin, and then cooled to room temperature to obtain a precursor mixture (A3) of an epoxy resin composition. 0.1 part of TPAP (B2) was added as a polymerization catalyst to 100 parts of the precursor mixture (A3) preheated to 80°C, and mixed for 2 minutes under vacuum conditions (vacuum degree 4 kPa) at a rotation speed of 2000 rpm using a planetary centrifugal mixer (Awatori Rentaro, ARV-310, manufactured by Shinki Corporation). After mixing, the mixture was quickly removed and immediately cooled to 40°C or lower to obtain an epoxy resin composition. The obtained epoxy resin composition was heated to 80°C, and applied to a release paper (casting paper for carbon fiber composite materials, manufactured by Lintec Corporation) as a film substrate using an applicator preheated to a predetermined temperature to obtain a resin film coating. The reinforcing fiber D1 was arranged in parallel to the resin composition-coated surface of the obtained resin film, and the resin composition-coated surface of another resin film was placed on top of it to form a sandwich structure. This was passed through a heated roll at 100°C for impregnation to obtain a prepreg with a resin content Rc of 35%. Furthermore, 13 sheets of the obtained prepregs were laminated with the same fiber orientation direction, then sandwiched between release films and vacuum pressed at 160°C, 0.1 MPa, and 360 minutes using a vacuum press to obtain a fiber-reinforced plastic. The Mw of the obtained fiber-reinforced plastic was 60,000, the solvent resistance was × (fail), the flexural strength was 105 MPa, and the flexural modulus was 5.8 GPa.
[0061] Comparative Example 2 100 parts of polylactic acid (A4) was weighed into a glass container, and 150 parts of chloroform was added to dissolve it. The polylactic acid solution was applied to a stainless steel plate coated with a release agent using a 100 μm coater, and dried in a circulating oven at 200° C. for 30 minutes to obtain a resin film with a thickness of 30 μm. Carbon fibers (D1) were arranged in parallel to the obtained resin film as reinforcing fibers, and the film was placed in a press (MP-WN, manufactured by Toyo Seiki Seisakusho) and pressed at 200°C and 0.1 MPa for 3 minutes to obtain a sheet material with a resin content Rc of 33%. After laminating 13 sheets with the same fiber orientation direction, they were sandwiched between release films and vacuum pressed at 200°C, 3.0 MPa, and 60 minutes using a vacuum press to obtain a fiber-reinforced plastic. The Mw of the obtained fiber-reinforced plastic was 200,000, the solvent resistance was ○ (passed), the flexural strength was 60 MPa, and the flexural modulus was 4.5 GPa.
[0062] Examples 2 to 7 The ingredients were blended in the amounts (parts) of the formula in Table 1, and a cyclic ester composition, a composition film, a prepreg, and a fiber-reinforced plastic were obtained under the same operations and conditions as in Example 1. The evaluation results of each are shown in Table 1. When stearyl alcohol (C1) was used, it was added simultaneously with B1. In Example 4, 11 sheets of the obtained prepregs were laminated, in Example 5, 17 sheets of the obtained prepregs were laminated, and in Example 6, 5 sheets of the obtained prepregs were laminated, and then a fiber-reinforced plastic was obtained by vacuum pressing.
[0063] [Table 1]
Claims
1. A prepreg using a cyclic ester composition containing a cyclic ester compound and a polymerization catalyst, and reinforcing fibers.
2. 2. The prepreg according to claim 1, wherein the cyclic ester compound is at least one selected from lactones and / or dilactones.
3. 2. The prepreg according to claim 1, wherein the cyclic ester compound is at least one selected from the group consisting of ε-caprolactone, glycolide and lactide.
4. The prepreg according to claim 1, wherein the polymerization catalyst is a compound containing at least one metal element selected from the group consisting of alkaline earth metals, rare earth metals, third period transition metals, aluminum, germanium, tin, and antimony, and / or a carboxylate, alkoxide, aryloxide, or β-diketone enolate of the metal element in the compound.
5. 2. The prepreg according to claim 1, wherein the polymerization catalyst is at least one selected from tin octylate, titanium tetraisopropoxide, and aluminum triisopropoxide, and the cyclic ester compound is at least one selected from ε-caprolactone, glycolide, and lactide.
6. 2. The prepreg according to claim 1, wherein the reinforcing fibers have a fiber length of 10 mm or more.
7. The prepreg according to claim 1 , wherein the cyclic ester composition has a viscosity at 100° C. of 100 Pa·s or less.
8. A fiber reinforced plastic using the prepreg according to any one of claims 1 to 7.
9. A method for producing a fiber-reinforced plastic according to claim 8, a mixing step of mixing a cyclic ester compound with a polymerization catalyst to obtain a mixture; a prepregging step of obtaining a prepreg from the mixture and reinforcing fibers; a polymerization step of causing ring-opening polymerization of a cyclic ester compound in the prepreg; A method for producing a fiber-reinforced plastic, comprising:
Citation Information
Patent Citations
Method for producing fiber-reinforced thermoplastic plastic and fiber-reinforced thermoplastic prastic
WO2004060981A1